Income distribution, efficiency and rationing - Yilmaz, Ensar (ELSEVIER, 2011)
This paper studies the impacts of income distribution on the efficiency of trade mechanism and rationing of agents who are priced out of trade in a dynamic search model with two-sided asymmetric information. Buyers and sellers have asymmetric information about valuations and incomes respectively. In such a frictional environment, the effects of several variants of changes in income distribution on efficiency of trading mechanism and the population of rationed buyers and sellers are elaborated. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Income distribution; Efficiency; Rationing; Search; PRICE-COMPETITION; MARKET; INEQUALITY; RISK; Business & Economics